Prevention of Risk of Falls and Musculoskeletal Disorders in Older People through Ergonomic exercise and Posture Screening - Hasyar, Andi Rizky Arbaim; Putri, Melda; Ahsaniyah, Andi Besse; Pudjiningrum, Andi Rahmaniar Suciani; Mustari, Yery; Hamisah, Hamisah; Rini, Ita; Hasbiah, Nurhikmawaty (Jurnal Abmas Negeri (JAGRI), 2025)
Aging is a natural process in the human life cycle. The increase in life expectancy has a positive impact on quality of life, but it also brings various consequences, one of which is the decline in physical and cognitive functions. As they age, the elderly become more susceptible to musculoskeletal disorders, which in turn increase the risk of falling. This community service activity aimed to enhance the understanding and awareness of the elderly regarding the importance of preventing falls and musculoskeletal disorders through ergonomic education and posture screening. The activity, themed "Ergonomics for Elderly Safety," was organized by the Physiotherapy Study Program, Faculty of Nursing, Hasanuddin University, on December 15, 2023, at the Tamalanrea Health Center, involving 30 elderly participants from the Prolanis program. The series of events included ergonomic counseling, demonstrations of ergonomic exercises, and posture screening using the Functional Reach Test and the Apley Scratch Test. The results of the Functional Reach Test showed an average reach of 26,88 cm, indicating a low risk of falling. Meanwhile, the Apley Scratch Test results revealed an average reach of 9,82 cm for the right arm and 16,95 cm for the left arm, reflecting the presence of musculoskeletal disorders, particularly in the left upper extremity. These findings highlight the importance of continuing ergonomic education and posture screening programs as part of preventive efforts to reduce the risk of falls and musculoskeletal disorders in the elderly.